Stadskyrkogårdar - Josefsson, Joakim (2011)
This master thesis is a study of how city cemeteries can be used and contributes to a socially sustainable urban development. Today sustainable development and sustainable urban development is something that more or less every organization is working with. Therefore it is also relevant to integrate our cemeteries in this work so that they can become a part of the sustainable urban development process. The thesis gives a basic understanding of sustainability as a concept and also defines socially sustainable (urban) development. The work then immerse itself in various types of park structures and how the relationship between the human individual and the public space work, to satisfy the needs that different people have. The literature study that has been made is also the base for the design of the walking interview that has been made for the two city cemeteries. The cemeteries that where studied where the Assistens cemetery in Copenhagen and the Eastern cemetery in Gothenburg. For these cemeteries a connoisseur was used for the walking interviews. This has shown how urban cemeteries, at a size of about 20 hectares, can be used in different ways by people from the city. Although the two cemeteries that have been studied differ, there are similarities in the characteristics, in both of them. For example, the two cemeteries both function as a transport route in the city. And there are also similarities in functions and characteristics that can be found in Berggren-Bärring's & Graham's park characters. The message that the paper will add to the discussion of city cemeteries and de development of sustainable urban development is the importance of integrating and understanding the need of the people who live in the city. This can be done not only by communication between those that visit graves at the cemeteries and the cemetery managers, but also between urban planners and residents of the city in general.